Lifestyles and cycling. - (:unkn) unknown (My University, 2012)
The report highlights different ways of bicycle use concerning age, milieu, lifestyles, and socio-economic factors in Germany. (Difu)
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsmittelwahl; Fahrradnutzung; Lebensstil; Multimodalität; Fahrradbenutzung; Mobilitätsverhalten